2005
DOI: 10.1007/bf03030569
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated with oligosaccharide and sucrose contents in soybean (Glycine max L.)

Abstract: Oligosaccharides and sucrose are very important nutritional components in soybean seeds. However, little information is available about their inheritance. We used molecular markers to identify the genomic regions significantly associated with the quantitative trait locus (QTL) that controls oligosaccharide and sucrose contents in segregating F2.10 RI lines. Two related, but independent, QTLs were identified for oligosaccharides --near marker satt546 on linkage group (LG) Dlb+W and satt278 on LG L. Four others,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
53
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 21 publications
4
53
2
Order By: Relevance
“…However, the genotype and location effects were greater than other sources of variation when comparing variance components. The heritability of sucrose in this study (0.74) was similar to that reported by Maughan et al (2000) and Kim et al (2005). This was also supported by the fact that lines in the mapping population ranked similarly across locations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the genotype and location effects were greater than other sources of variation when comparing variance components. The heritability of sucrose in this study (0.74) was similar to that reported by Maughan et al (2000) and Kim et al (2005). This was also supported by the fact that lines in the mapping population ranked similarly across locations.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison with the reference 'Williams 82' physical map, these two QTL regions were within a similar proximity, with sucrose QTL in the F 3derived population being narrowed down to a smaller region in the SNP analysis (Table 8). In other studies, sucrose QTL were mapped by Kim et al (2005Kim et al ( , 2006 using data from only one location. In a previous study, a sucrose QTL flanked by Satt287 (at 1,631,658-1,631,885 bp of Gm16 in the Williams 82 physical map) and Sct_065 (at 10,498,889-10,499,048 bp of Gm 16, Williams 82) on chromosome 16 was identified by Kim et al (2006); this previously reported QTL was distantly located upstream from the QTL identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These explained a relatively low amount of phenotypic variation (< 10%) in sucrose content. However, they did not detect the QTL previously reported by Kim et al (2005), even though the high-sucrose parent used to derive populations was the same in both studies. Skoneczka et al (2009) identified a QTL on chromosome 6 (MLG C2), flanked by markers Sat213 and Satt643, which was responsible for low-stachyose and high-sucrose contents in PI 200508.…”
contrasting
confidence: 64%
“…No epistasis was observed among the identified sucrose QTL. Kim et al (2005) reported four QTL located on three chromosomes (2, 11 and 19) for sugar content using RIL populations derived from the cross of 'Keunolkong' 9 'Shinpaldalkong'. The major QTL, flanked by SSR markers Satt278 and Satt523, located on chromosome 19 explained 21.4% of the total phenotypic variation in sucrose content, while the other two QTL on chromosome 2 and 11 conferred minor effects, respectively.…”
mentioning
confidence: 98%
“…Kim et al. () identified two common QTL for oligosaccharide and sucrose in a recombinant inbred line (RIL) population. Utilizing F 2:3 population consisting 170 lines, Wang et al.…”
mentioning
confidence: 99%